Anti-oxidative and anti-inflammatory activity of Achatina fulica mucus in streptozocin-nicotinamide-induced diabetic kidney disease: an animal model study - Wachid Putranto; Gigih Fitriawan; Ratih Tri Kusuma Dewi; Aryo Suseno; Arief Nurudhin; Yulyani Werdiningsih; Santy Ayu Puspita Perdhana; Nurhasan Agung Prabowo; Yeremia Suryo Pratama (Journal of Nephropathology)
Introduction: Diabetic kidney disease (DKD) progression resulted in increased intrarenal oxidative stress and increased inflammatory resulting in further renal fibrosis. Achatina fulica mucus was regarded to exerts anti-oxidative and anti-inflammatory effect. Objectives: This study aims to observe the effect of administration of A. fulica mucus on oxidative stress and inflammation biomarkers in DKD-induced rats. Methods and Materials: In this study, we used 32 males white Wistar rats divided into four groups; a control, and other three different groups induced with 45 mg/kg streptozocin (STZ) and 110 mg/kg nicotinamide (NA) intra-peritoneally. Achatina fulica mucus was administered orally in the last groups; 3.5 mL/d (S1), and 7 mL/d (S2). Post-test measurement of inflammatory and oxidative biomarker was used to determine the outcome. Results: The study resulted in reduction of malondialdehyde (MDA), transforming growth factor-β (TGF-β), tumor necrosis factor-α (TNF-α), high sensitivity C-reactive protein (hs-CRP), vascular endothelial growth factor (VEGF), and interleukin-1β (IL-1β) in A. fulica mucus administration in our STZ-NA induced rats, with higher dose of the mucus further reduce the inflammatory and oxidative stress biomarkers. Conclusion: Current study showed the potential of A. fulica mucus usage in future management of inflammation and oxidative stress in diabetes and DKD.